Hubungan Stunting terhadap Perkembangan Motorik Balita - Baiq Ricca Afrida; Ni Putu Aryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Stunting is a problem in growth that occurs at the age of children after 2 years which is a result of lack of nutrition during pregnancy. This study aims to determine the relationship between stunting and motor development of toddlers in Indonesia. The method used is a systemic literature review of various journals and books. After selecting the PRISMA Checklist on three data bases, namely ProQuest Pubmed and Google Scholar, thirteen journals were obtained that match the inclusion criteria. Based on the results of the review from the journal, the results showed that there was a relationship between stunting and motor development of toddlers